EEG responses induced by cerebellar TMS at rest and during visuomotor adaptation - Po-Yu Fong; Danny Spampinato; Kevin Michell; Marco Mancuso; Katlyn Brown; Jaime Ibáñez; Alessandro Di Santo; Anna Latorre; Kailash Bhatia; John C Rothwell; Lorenzo Rocchi (NeuroImage, 2023)
Background: Connections between the cerebellum and the cortex play a critical role in learning and executing complex behaviours. Dual-coil transcranial magnetic stimulation (TMS) can be used non-invasively to probe connectivity changes between the lateral cerebellum and motor cortex (M1) using the motor evoked potential as an outcome measure (cerebellar-brain inhibition, CBI). However, it gives no information about cerebellar connections to other parts of cortex. Objectives: We used electroencephalography (EEG) to investigate whether it was possible to detect activity evoked in any areas of cortex by single-pulse TMS of the cerebellum (cerebellar TMS evoked potentials, cbTEPs). A second experiment tested if these responses were influenced by the performance of a cerebellar-dependent motor learning paradigm. Methods: In the first series of experiments, TMS was applied over either the right or left cerebellar cortex, and scalp EEG was recorded simultaneously. Control conditions that mimicked auditory and somatosensory inputs associated with cerebellar TMS were included to identify responses due to non-cerebellar sensory stimulation. We conducted a follow-up experiment that evaluated whether cbTEPs are behaviourally sensitive by assessing individuals before and after learning a visuomotor reach adaptation task. Results: A TMS pulse over the lateral cerebellum evoked EEG responses that could be distinguished from those caused by auditory and sensory artefacts. Significant positive (P80) and negative peaks (N110) over the contralateral frontal cerebral area were identified with a mirrored scalp distribution after left vs. right cerebellar stimulation. The P80 and N110 peaks were replicated in the cerebellar motor learning experiment and changed amplitude at different stages of learning. The change in amplitude of the P80 peak was associated with the degree of learning that individuals retained following adaptation. Due to overlap with sensory responses, the N110 should be interpreted with caution. Conclusions: Cerebral potentials evoked by TMS of the lateral cerebellum provide a neurophysiological probe of cerebellar function that complements the existing CBI method. They may provide novel insight into mechanisms of visuomotor adaptation and other cognitive processes.